The art of communicating on paper - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The verb to communicate has a lot of synonyms: speaking, divulging, passing on, publishing, conveying, explaining, informing, exchanging, corresponding To communicate is more than just being in contact with the outside world a simple...